Short-term versus long-term antiarrhythmic drug treatment after cardioversion of atrial fibrillation (Flec-SL): a prospective, randomised, open-label, blinded endpoint assessment trial - Kirchhof, Paulus; Borggrefe, Martin (The lancet, 2012)
Summary Background: Antiarrhythmic drugs prolong the atrial action potential and refractory period, and thereby prevent recurrent atrial fibrillation after cardioversion. The atrial action potential normalises after 2-4 weeks of sinus rhythm, suggesting that antiarrhythmic drugs might not be needed beyond that period. Therefore, we investigated whether short-term antiarrhythmic drug treatment after cardioversion is non-inferior to long-term treatment. Methods: We enrolled patients in a prospective, randomised, open-label, blinded endpoint assessment trial between May 4, 2007, and March 12, 2010, at 44 centres in Germany. Eligible patients were adults with persistent atrial fibrillation undergoing planned cardioversion. After successful cardioversion, patients were randomly assigned in permuted blocks of six per centre to: no antiarrhythmic drug treatment (control); treatment with flecainide (200-300 mg per day) for 4 weeks (short-term treatment); or flecainide for 6 months (long-term treatment). The primary endpoint was time to persistent atrial fibrillation or death. Patients and clinicians were unmasked to group assignment and treatment. The primary outcome was assessed in a core laboratory, members of which were masked to treatment group. Patients were monitored for 6 months by daily telemetric electrocardiograph (ECG) and centrally adjudicated Holter ECG recordings whenever atrial fibrillation was noted in two consecutive ECGs. Analyses were per protocol. This trial is registered, number ISRCTN62728742. Findings: After assay sensitivity was established with 4-week follow-up data from 242 patients showing that flecainide was superior to no treatment (Kaplan-Meier survival 70·2% vs 52·5%; p=0·0160), the trial continued to compare short-term versus long-term treatment. The primary outcome occurred in 120 (46%) of 261 patients receiving short-term treatment and in 103 (39%) of 263 patients receiving long-term treatment (event-free survival 48·4% [95% CI 41·9-55·0] vs 56·4% [49·1-63·6]; Kaplan-Meier estimate of difference 7·9% [-1·9 to 17·7]; p=0·2081 for non-inferiority; margin prespecified at 12%). In a post-hoc landmark analysis of patients who had not reached the primary endpoint in the first month, long-term treatment was superior to short-term treatment (Kaplan-Meier estimate of difference 14·3% [5·1-23·6]; hazard ratio 0·31 [0·18-0·56]; p=0·0001). Interpretation Short-term antiarrhythmic drug treatment after cardioversion is less effective than is long-term treatment, but can prevent most recurrences of atrial fibrillation. Funding The German Federal Ministry of Education and Research, Deutsche Forschungsgemeinschaft, 3M Medica, and MEDA Pharmaceuticals.